ANALISIS RISIKO K3 PADA JASA KEPELABUHAN DENGAN METODE HIRARC (HAZARD IDENTIFICATION RISK ASSESMENT AND RISK CONTROL) - Ramdhani A., A Nur Shafirah; Liperda, Rahmad Inca; Ruswandi, Nanda (Universitas Majalengka, 2023)
PT. Pelabuhan Indonesia (Pelindo) is a world-class port offering integrated services between Indonesian ports. The establishment of Perind as a result of this integration is a strategic initiative of the government as a shareholder to realize national connectivity and a stronger logistics ecosystem network. This study was conducted with the aim of identifying hazards, assessing risks, and managing port service activities. Use HIRARC (Hazard, Identification, Risk Assessment and Risk Management) and SWOT (Strength, Weakness, Opportunity, and Threat) methods to identify hazards and perform risk assessments. With the use of the HIRARC method, 10 potential risks were found in one green risk assessment indicating that the potential problem was moderate. For inventory warehouse personnel activities, the value is 3, and the warehouse worker or worker unloading value is 3. Mixed strategies can be found in the four quadrants of analysis using SWOT for the following purposes: Improving and improving the quality of the company.